Educational Values in QS. Al-Kahf Verses 60–82: Analysis of Hermeneutic Studies on Ibnu Katsir’s Tafsir - Afkar Hanif Syaifuddin; Faridi Faridi; Sunarto Sunarto (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study examines in depth the Tafsir of Ibn Kathir on educational values by interpreting the meaning of the text in depth in Surah Al-Kahfi verses 60-82, through contextual analysis, exploring its relevance to contemporary educational challenges, and formulating its implementation strategy in the context of modern education. Through a qualitative approach to literature with the method of hermeneutic analysis ijmali (global) in the chronology and dialogue of the Prophet Musa's search for knowledge to the Prophet Khidir as. The series of verses about events from the beginning of the story of the search for a teacher to the meeting of the two, in the interpretation of Ibn Kathir contains many educational values, exemplary attitudes, to character formation that are still relevant and needed today. The educational values in it are summarized in the values; 1) Education of Monotheism in the form of an attitude of faith, a reflection of the Omnipotence of Allah SWT and the weakness of human knowledge, 2) Worship Education as a real manifestation of obedience. 3) Moral Education to form moral and ethical awareness. 4) Community Education (social) to form a sense of social and environmental concern, and also contains 5) Rabbani character education that reflects the formation of Quranic attitudes.